X-inactive-specific transcript of peripheral blood cells is regulated by exosomal Jpx and acts as a biomarker for female patients with hepatocellular carcinoma. (November 2017) - Ma, Xiang; Yuan, Tingdong; Yang, Chao; Wang, Zusen; Zang, Yunjin; Wu, Liqun; Zhuang, Likun
Background: Long noncoding ribonucleic acid (lncRNA) X-inactive-specific transcript (Xist) was reported to affect cell proliferation and metastasis in hepatocellular carcinoma (HCC). However, there are rare reports focusing on the diagnostic evaluation and regulatory mechanism of Xist expression from peripheral blood cells of patients with HCC. Methods: In this study, a cohort of 206 female participants including healthy volunteers (HVs) and patients with chronic hepatitis B (CHB), cirrhosis and HCC was recruited. Coculture system was used to evaluate the effects of exosomal JPX transcript, XIST activator (Jpx) on Xist expression of blood cells. Results: First, Xist expressions of both peripheral blood mononuclear cells and granulocytes were upregulated in female patients with HCC, and showed significantly increased discriminatory power when differentiating female patients with early-stage HCC from controls or differentiating female patients with HCC from patients with CHB and cirrhosis, compared with alpha fetoprotein (AFP). Then, another lncRNA Jpx that was an activator of Xist was upregulated in exosomes, mononuclear cells and granulocytes of female patients with HCC. Furthermore, our results showed that Jpx could be delivered from HCC cells to blood cells via exosomes and activate Xist expression of blood cells by repressing the transregulatory effects of CCCTC-binding factor (CTCF). Conclusions: This study revealed an exosome-mediated regulation of Xist expression in blood cells and suggested that Xist expressions of mononuclear cells and granulocytes would be promising biomarkers for diagnosis of female patients with HCC.